1992
DOI: 10.2466/pr0.1992.71.3f.1075
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis of Weight-Loss Behavior

Abstract: This study used a theoretical framework with multiple variables in multivariate analyses (factor, multiple regression, and path analyses) to investigate the sociopsychological predictors of weight loss. Responses from 309 participants of a comprehensive weight-loss program indicated that self-assurance was the most significant predictor of actual weight loss, followed by weeks completed. Other factors, such as program satisfaction and perceived importance, indirectly predicted weight loss through the interveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Other studies have shown larger weight loss goals to positively predict weight loss [41,52] and in one other case goals had small predictive value [53]. Collectively, previous results and those we now report suggest that positive and moderate expectations/outcome evaluations foretell the best overall results, particularly if accompanied by a high sense of self-assurance [52]. …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Other studies have shown larger weight loss goals to positively predict weight loss [41,52] and in one other case goals had small predictive value [53]. Collectively, previous results and those we now report suggest that positive and moderate expectations/outcome evaluations foretell the best overall results, particularly if accompanied by a high sense of self-assurance [52]. …”
Section: Discussionsupporting
confidence: 72%
“…Positive expectations expressed as a higher reported likelihood of reaching goal weight predicted larger short-term weight loss in subjects who showed lower level of fantasizing and daydreaming about beneficial consequences of large weight loss [51]. Other studies have shown larger weight loss goals to positively predict weight loss [41,52] and in one other case goals had small predictive value [53]. Collectively, previous results and those we now report suggest that positive and moderate expectations/outcome evaluations foretell the best overall results, particularly if accompanied by a high sense of self-assurance [52].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of predictors of weight loss and weight maintenance have been conducted and presented in the literature. Predictors of greater weight loss may include greater initial weight (19,22), greater weight loss at the end of the first week (l), greater weight loss during a 3-week diet only period (23), greater weight loss during the first month of therapy (22), older age of onset of obesity (19), greater self-assurance (15), higher social conformity (16), greater number of past weight loss attempts (l), greater patient motivation as estimated by the physician (23), less responsiveness to external cues (16), larger monthly weight loss goal (l), greater adherence to treatment (17,23), more frequent contact by the therapist (12,22), visiting the clinic for a longer time though less frequently (19), greater number of treatment weeks completed (IS), keeping food records (20), binge eating at night (23), structured eating in a day treatment facility (2), and being male (19), Caucasian (19), younger (19), or single (19). Type of OBESITY RESEARCH Vol.…”
Section: Introductionmentioning
confidence: 99%